2006
DOI: 10.1038/sj.eye.6702442
|View full text |Cite
|
Sign up to set email alerts
|

The use of colour Doppler imaging in the diagnosis of retinal detachment

Abstract: Design Prospective study. Purpose To evaluate real-time duplex colour Doppler examination with colour and pulse Doppler ultrasonography (US) (colour Doppler imaging (CDI)) for detection of the retinal detachment from membranous structures in the posterior segment. Materials and methods In 33 consecutive patients with ophthalmoscopically invisible eyes (34 eyes), CDI was performed to detect the presence or absence of retinal detachment. The diagnostic criterion for retinal detachment was whether or not spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…It has been shown that detecting the presence of vascularity within a detached retina and documenting the lack of vascularity in vitreous membranes using colour Doppler imaging (CDI) can differentiate retinal detachments from vitreous membranes (Wong and others 1991, Stefanczyk and others 1996, Ido and others 2007). In veterinary medicine, contrast‐enhanced ultrasonography (CEU) using stabilised microbubble contrast agents has been used to improve the detection of vascularity within organs (Haers and Saunders 2009), but to the authors’ knowledge, the use of CEU has not been reported for the ocular examinations in veterinary patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that detecting the presence of vascularity within a detached retina and documenting the lack of vascularity in vitreous membranes using colour Doppler imaging (CDI) can differentiate retinal detachments from vitreous membranes (Wong and others 1991, Stefanczyk and others 1996, Ido and others 2007). In veterinary medicine, contrast‐enhanced ultrasonography (CEU) using stabilised microbubble contrast agents has been used to improve the detection of vascularity within organs (Haers and Saunders 2009), but to the authors’ knowledge, the use of CEU has not been reported for the ocular examinations in veterinary patients.…”
Section: Introductionmentioning
confidence: 99%
“…[8,16] Studies examining changes in ocular blood flow velocities in RD are limited. [10] Ido et al found the usefulness of CDUS in the diagnosis of RD in the presence of hazy media. [10] Similar to ours, in their study, the absence or presence of RD was confirmed during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[8] RD was described as visualization of a flow signal (presence of vascularity) along the detached retina, while vitreous membranes were described as lack of vascularity. [10]…”
Section: Doppler Ultrasound Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…CDI can be used to differentiate rhegmatogenous retinal detachment from vitreous membranes in cases where ophthalmoscopy is not feasible. 65,66 Some authors suggest that contrast enhancement improves the accuracy of CDI in such cases. 67 The blood flow velocity in the retrobulbar central retinal, short posterior and ophthalmic arteries was decreased in eyes with retinal detachment compared to those of control subjects.…”
Section: Colour Doppler Imaging In Retinal Detachmentmentioning
confidence: 99%